2015
DOI: 10.37237/060403
|View full text |Cite
|
Sign up to set email alerts
|

About a Boy: A Gamer and L2 English Speaker Coming into Being by Use of Self-Access

Abstract: This is an interview study of Eldin, a 14-year-old Bosnian boy living in Sweden since the age of six. The aim is to investigate how Eldin became a gamer and how he, strongly motivated, learned foreign/second (L2) English mainly through self-access gameplay. Using language learning motivation theories, Dörnyei’s (2005, 2009) L2 Motivational Self System and Dweck’s (2006) concept of mindsets, the questions are: (i) By whom and at what age was the learner introduced to video games?, (ii) What was it about the gam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…As part of the Early Language Learning in Europe (ELLiE) Project, a largescale study spanning seven European countries, Muñoz and Lindgren (2011) examine language exposure and improvement in ten to eleven year-old children, based on out-of-school activities. Results tend to support those of the smaller studies discussed above in that learners' language improved through various activities, mainly computer games, subtitled TV/films, the internet, music, and radio (Sundqvist, 2015).…”
Section: Self-access Through Gaming and Other Mediasupporting
confidence: 71%
See 1 more Smart Citation
“…As part of the Early Language Learning in Europe (ELLiE) Project, a largescale study spanning seven European countries, Muñoz and Lindgren (2011) examine language exposure and improvement in ten to eleven year-old children, based on out-of-school activities. Results tend to support those of the smaller studies discussed above in that learners' language improved through various activities, mainly computer games, subtitled TV/films, the internet, music, and radio (Sundqvist, 2015).…”
Section: Self-access Through Gaming and Other Mediasupporting
confidence: 71%
“…Recently, there have been several studies on self-access in which young learners (ranging in age from ten to fourteen years old) demonstrated academic improvement in English from having played online multi-player video games outside of school (Jeon, 2014;Piirainen-Marsh & Tainio, 2009;Sundqvist, 2015;Sundqvist & Sylvén, 2014). Sundqvist and Sylvén (2014) found that Swedish learners of English demonstrated improvement in speaking and vocabulary through out-of-school gaming.…”
Section: Self-access Through Gaming and Other Mediamentioning
confidence: 99%
“…To date, quantitative methods are frequently used in EE research, but combining quantitative and qualitative methods by adopting a mixed-methods approach also occurs (e.g., Lai & Zheng, 2018;Schwarz, 2020;Sundqvist, 2019). Some studies are qualitative interview studies (e.g., Soyoof, 2023;Sundqvist, 2015), at times ethnographically oriented (Hannibal Jensen, 2019;Rothoni, 2017). An advantage of interviews is that they yield in-depth data, and such data are needed to shed light on learners characterized by high, mid, and low EE engagement and why they choose (not) to be involved in EE.…”
Section: Methods Research Instruments and Ways Forwardmentioning
confidence: 99%
“…Furthermore, and most importantly, video games also foster the socio-cognitive process of learning and language socialization (e.g., Piiranen-Marsh & Tainio, 2009;Zheng et al, 2009), and vocabulary development as a by-product of playing video games (Fajt & Vékási, 2022;Hitosugi et al, 2014;Neville, 2010;Sundqvist & Sylvén, 2012) or even communicating with other players online (Sundqvist, 2015). Similarly to other EE activities, video games also provide contextualized environments for learners to comprehend and process L2 input and transform it into intake through noticing, catering for incidental learning to take place (Schmidt, 1990(Schmidt, , 1994(Schmidt, , 1995.…”
Section: Video Gamesmentioning
confidence: 99%
“…Most boys reported that they play video games regularly, and identified as gamers while only one girl did the same. Pál pointed out that as most video games are in English, when it comes to online gaming, the language used for intercultural communication is almost exclusively the English language and this kind of online communication and gaming in general provides a plethora of linguistic input and, therefore, could result in incidental L2 learning (Chik, 2014;Ryu, 2011;Ryu, 2013;Sundqvist, 2015). He explained this as follows: This could ultimately increase player L2 learning motivation (Bytheway, 2015;Ebrahimzadeh & Sepideh, 2017) as the inner desire to comprehend the story and to achieve the goals set in a video game may motivate players to check previously unknown vocabulary items in order to improve their general L2 proficiency.…”
Section: Video Gamesmentioning
confidence: 99%